Satellite attitude tracking control using Lyapunov control theory - Okasha, Mohamed Elsayed Aly Abd Elaziz; Idres, Moumen; Ghaffar, Alia (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper explores attitude control algorithms using thrusters and momentum wheels for satellite tracking manoeuver. The attitude reference trajectory is generated to track a ground object on the rotating Earth and to keep the Sun vector perpendicular to the solar panel to maximize the solar power. The dynamic model is derived based on Newton-Euler approach and Modified Rodrigues Parameters (MRPs) are used to represent attitude kinematics. The control algorithms are derived based on the Lyapunov stability control theory to ensure the asymptotic stability of the control law. MATLAB software package is used as a simulation environment to develop and test the performance of the proposed tracking control algorithms using a Graphical User Interface (GUI) tool that can be expanded for future development.